The Influence of Trust, Customer Satisfaction, and Promotion on Brand Loyalty of Samsung Smartphones: Case Study on Students of the Faculty of Economics and Business, Universitas Malikussaleh - Sylfiyatul Hulfa Zalza; Samsul Bahri; Adnan; Ikramuddin (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of trust, customer satisfaction, and promotion on brand loyalty of Samsung smartphones among students of the Faculty of Economics and Business, Universitas Malikussaleh. Trust, customer satisfaction, and promotion were selected as independent variables because they are considered key factors in shaping consumer loyalty, while brand loyalty serves as the dependent variable, reflecting consumers’ commitment to a specific product. Primary data were collected through questionnaires distributed to students who have purchased or used Samsung smartphones, employing purposive sampling to ensure that respondents met the research criteria. Data analysis was conducted using multiple linear regression, allowing the identification of the effect of each independent variable on brand loyalty both partially and simultaneously. The results indicate that trust, customer satisfaction, and promotion have a positive and significant effect on brand loyalty. In other words, higher levels of consumer trust in Samsung’s quality and services, greater customer satisfaction with the product, and more effective promotional strategies increase the likelihood that consumers remain loyal to the Samsung brand. These findings provide important insights into the main factors influencing consumer loyalty and serve as a strategic reference for companies to design more targeted marketing programs, enhance brand loyalty among students as potential long-term consumers, and contribute valuable academic knowledge for future studies in the field of consumer behavior and brand management.